Evidence of nonlinearity in presence of external forcing and magnetic field in a glow discharge plasma. (May 2017) - Saha, Debajyoti; Shaw, Pankaj Kumar; Ghosh, Sabuj; Janaki, M.S.; Sekar Iyengar, A.N.
Abstract: We implement different statistical analysis techniques to investigate the presence of nonlinearity in the fluctuations of a steady state glow discharge plasma (GDP). We introduce a novel 'delay vector variance' analysis (DVV) to allow reliable detection of nonlinearity in a plasma in presence of external forcing and magnetic field by providing some easy to interpret diagrams. The analysis has also been implemented to study numerically simulated results for the first time. An estimate of the Zscore has been carried out to detect the presence of nonlinearity in a somewhat quantitative sense. An informal test for bicoherency has been applied to detect the interaction amongst different modes obtained by performing emperical mode decomposition to strengthen the analysis on nonlinearity. The results obtained from bicoherency test resemble those obtained by performing DVV. An attempt to model the experimental observations by a second order nonlinear ordinary differential equation derived from the fluid equations of plasma has revealed convincing results.